Karakteristik Fisikokimia Tepung Pandan Tikar (Pandanus tectorius Park.): Physicochemical Characteristics of Flour Pandan Tikar (Pandanus tectorius Park.) - Budi Santoso; Nelci Welmina Menanti; Zita Letviany Sarungallo (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2021)
ABSTRACT Pandan tikar (Pandanus tectorius Park.) is one of pandanaceae that spread almost along the Pacific coast, contains high nutrients, variety in fruit colors and has a distinctive pandan flavor. Fruit of Pandan tikar is potentially to be processed into flour. This research aims was to determine the physico-chemical characteristic of flour fruit of pandan tikar. The results showed that the color of the flour varies from yellow to orange red, the density of 0,27-0,22%; solubility in water 52,58-61,65%; the temperature of the gelatinization of 89º-91ºC; water content 10,97-11,21%; ash 5,59-6,54%; fat 0,91-1,6%; protein 3,62-3,8%; carbohydrates 88,48-88,75%; as well as crude fiber 20, 98-21,47%; starch content 10,76-23,20%; β-carotene 588,69-2266,13 ppm; and total sugar 26,23-36,08%. ABSTRAK Pandan tikar (Pandanus tectorius Park.) merupakan salah satu jenis pandanaceae yang penyebarannya hampir di sepanjang pantai pasifik, mengandung zat gizi yang cukup tinggi, memiliki variasi warna buah dan memiliki citarasa khas pandan. Buah pandan tikar sangat berpotensi untuk diolah menjadi tepung. Penelitian ini bertujuan untuk menentukan sifat fisik dan kimia tepung dari 3 jenis buah pandan tikar dengan warna kuning, kuning tua, dan oranye. Hasil penelitian menunjukkan bahwa tepung yang dihasilkan dari tiga jenis buah pandan tikar memiliki dari warna kuning hingga merah-orange; densitas kamba 0,27-0,33%; kelarutan dalam air 57,58-61,65%; suhu gelatinisasi 89°-91°C; kadar air 10,97-11,21%; abu 5,59-6,54%; lemak 0,91-1,6%; protein 3,62-3,8; karbohidrat 88,48-88,75; serta kasar 20,98-21-47%; kadar pati 10,76-23,20; β-karoten 588,69-2266,13 ppm; dan total gula 26,23-36,08%.